2012
DOI: 10.1111/j.1365-2745.2011.01944.x
|View full text |Cite
|
Sign up to set email alerts
|

Forest productivity increases with evenness, species richness and trait variation: a global meta‐analysis

Abstract: Summary 1.Although there is ample support for positive species richness-productivity relationships in planted grassland experiments, a recent 48-site study found no diversity-productivity relationship (DPR) in herbaceous communities. Thus, debate persists about diversity effects in natural versus planted systems. Additionally, current knowledge is weak regarding the influence of evenness on the DPRs, how DPRs are affected by the variation in life-history traits among constituent species in polycultures and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

61
529
15
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 658 publications
(613 citation statements)
references
References 66 publications
(87 reference statements)
61
529
15
8
Order By: Relevance
“…Mixing of complementary tree species may increase stand productivity, mitigate the effects of drought and other risks, and increase the stability and the efficiency of resource use in forest production systems in response to climate change (Pretzsch et al 2015). Kelty (2006) and Zhang et al (2012) observed that mixtures are often much more productive than monocultures. However, there is a general scarcity of systematic empirical studies investigating the effects of mixing commercially important and widespread tree species.…”
Section: Introductionmentioning
confidence: 99%
“…Mixing of complementary tree species may increase stand productivity, mitigate the effects of drought and other risks, and increase the stability and the efficiency of resource use in forest production systems in response to climate change (Pretzsch et al 2015). Kelty (2006) and Zhang et al (2012) observed that mixtures are often much more productive than monocultures. However, there is a general scarcity of systematic empirical studies investigating the effects of mixing commercially important and widespread tree species.…”
Section: Introductionmentioning
confidence: 99%
“…For example, macroscale plant species richness patterns are a function of regional productivity gradients (Abrams 1995;Chase and Ryberg 2004; but see Adler et al 2011). Conversely, at local scales, increasing levels of plant diversity drive increased production of biomass (Tilman et al 2001;Reich et al 2001aReich et al , 2012van Ruijven and Berendse 2003;Roscher et al 2005;Isbell et al 2011;Zhang et al 2012) because higher diversity communities contain a larger number of species with unique traits ) and competition strategies. As increasing numbers of species co-occur in an assemblage, their complementary resource acquisition strategies use overall resource pools more completely.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of this study, we focus on the wellestablished positive relationship between local species richness and biomass production (Tilman et al 2001;Reich et al 2001a;van Ruijven and Berendse 2003;Roscher et al 2005;Isbell et al 2011;Zhang et al 2012). We predict that when applied to woody encroachment into grasslands, declining levels of herbaceous species diversity associated with global change can drive lower levels of biomass production (Schnitzer et al 2011) and decreased competition for resources (Tilman et al 1997a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Community diversity 120 The importance of species richness and evenness in influencing diversity-associated 121 productivity has been demonstrated in a meta-analysis of 54 studies (Zhang et al 2012 (Parker & Peet 1984). Lacking of analytic wood data, we adopted DBH structures of P.…”
mentioning
confidence: 99%